PENDIDIKAN KARAKTER DALAM MEMBANGUN KEMANDIRIAN SISWA - Ena Suma Indrawati; Lelfita; Laspida Harti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of character education in fostering student independence in schools through the integration of a curriculum that instills character values such as discipline, responsibility, and honesty. Based on a literature review of articles published between 2020 and 2025, it was found that well-structured character education can enhance student independence by strengthening their sense of responsibility and ability to make independent decisions. Additionally, character education contributes to the development of positive social behavior, including increased empathy and interpersonal skills among students. However, challenges in implementing character education in practice, particularly related to teacher training and family support, remain significant barriers. This study recommends that schools adopt project-based approaches that integrate character values into learning, as well as strengthen collaboration between schools, families, and communities. The findings also suggest the need for further research on the role of technology in supporting character education and the development of student independence.